(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses the objectives of the subject Russian language, the features of the process of formation of foreign language speech activity and the components that determine its content - language material, theoretical information about the language and the skills to operate with them. Communication, speech skills; themes and situations, each of the named components performs its own functions.